Surviving Sepsis Campaign: Research Priorities for Sepsis and Septic Shock. Issue 8 (August 2018) - Coopersmith, Craig M.; De Backer, Daniel; Deutschman, Clifford S.; Ferrer, Ricard; Lat, Ishaq; Machado, Flavia R.; Martin, Greg S.; Martin-Loeches, Ignacio; Nunnally, Mark E.; Antonelli, Massimo; Evans, Laura E.; Hellman, Judith; et al.
Abstract : Objective: To identify research priorities in the management, epidemiology, outcome and underlying causes of sepsis and septic shock. Design: A consensus committee of 16 international experts representing the European Society of Intensive Care Medicine and Society of Critical Care Medicine was convened at the annual meetings of both societies. Subgroups had teleconference and electronic-based discussion. The entire committee iteratively developed the entire document and recommendations. Methods: Each committee member independently gave their top five priorities for sepsis research. A total of 88 suggestions (Supplemental Table 1, Supplemental Digital Content 2, http://links.lww.com/CCM/D636 ) were grouped into categories by the committee co-chairs, leading to the formation of seven subgroups: infection, fluids and vasoactive agents, adjunctive therapy, administration/epidemiology, scoring/identification, post-intensive care unit, and basic/translational science. Each subgroup had teleconferences to go over each priority followed by formal voting within each subgroup. The entire committee also voted on top priorities across all subgroups except for basic/translational science. Results: The Surviving Sepsis Research Committee provides 26 priorities for sepsis and septic shock. Of these, the top six clinical priorities were identified and include the following questions: 1) can targeted/personalized/precision medicine approaches determine which therapies will work for which patients at which times?; 2) what are ideal endpoints for volume resuscitation and how should volume resuscitation be titrated?; 3) should rapid diagnostic tests be implemented in clinical practice?; 4) should empiric antibiotic combination therapy be used in sepsis or septic shock?; 5) what are the predictors of sepsis long-term morbidity and mortality?; and 6) what information identifies organ dysfunction? Conclusions: While the Surviving Sepsis Campaign guidelines give multiple recommendations on the treatment of sepsis, significant knowledge gaps remain, both in bedside issues directly applicable to clinicians, as well as understanding the fundamental mechanisms underlying the development and progression of sepsis. The priorities identified represent a roadmap for research in sepsis and septic shock.